ROLE OF GRAIN STORAGE AND PROCESSING ENTERPRISES IN THE ECONOMY AND SPECIFIC CHARACTERISTICS OF THE ORGANIZATION OF ACCOUNTING IN THEM (World Economics and Finance Bulletin, 2024)
This article reveals the role of grain storage and processing enterprises in the economy and the specifics of accounting organization at them. Within the framework of the topic, the studies of economists were examined and conclusions and proposals on the topic were given.
Keywords: Grain Storage; Accounting; International Standard